Investigation on viscoelastic phase separation of phenolphthalein poly (ether ether ketone)/epoxy blends system. Issue 3 (March 2020) - Ding, Yanyu; Liu, Rui; Liu, Huashi
The phase morphology in thermoplastic (TP)/thermoset (TS) blends system plays a critical role in the improvement of composites toughness. In this article, the modified viscoelastic model coupling with the thermodynamic model was established to describe the dynamic process of polymerization-induced phase separation in TP/TS blends system, in which the effects of TS curing reactions, the chain-length asymmetry, and molecular dynamic asymmetry between TP and TS were considered. Based on developed model, simulations were implemented to study phase morphology formation in phenolphthalein poly(ether ether ketone) (PEK-C)/epoxy blends system, and the influences of different factors, including initial PEK-C volume fraction, bulk modulus of PEK-C resin, curing reaction of epoxy resin, and curing temperature, on the phase separation behavior were investigated. Also, the experiments were carried out to verify the simulation results. The results revealed that there was an induction period before phase separation started; afterward, the bi-continuous structure appeared in mixtures, in which small concentration differences existed between two phases. As the initial PEK-C concentration increased, the final phase morphology experienced a gradual transition from the islands-sea structure to the bi-continuous structure, and finally formed the phase-inverted structure. Moreover, it was found that the phase morphology evolution was influenced by viscoelastic effect of polymer molecules. As the bulk modulus of PEK-C increases, the blends system tended to organize into a bi-continuous structure and the phase-inverted morphology at a lower initial content of PEK-C.